Isolation and Identification of Escherichia coli O157:H7 from locally minced meat and imported minced and chicken meat: Zuhair.A.Mohammed , Fadia Abd AL-MuhsinAL-Khyat - Mohammed, Zuhair A. (The Iraqi Journal of Veterinary Medicine, 2008)
A total of 143 samples of meat were examined in this study, theserepresents 67 samples of locally minced meat, 31 samples of importedminced meat and 45 samples of imported chicken meat. The samples werecollected from different areas of Baghdad city during the period fromJanuary till May 2006.Detection, isolation an enumeration of E.coli 0157:H7 were carried out.The result revealed that there was a significant difference (P < 0.05) in theisolation percentage and the microbial counts of E.coli 0157:H7 whencomparing the three types of meat. The highest prevalence were found in thelocally minced meat (80% ; 1.6 x 107 cfu/g) Followed by the importedminced meat (65% ;5.9x106cfu/g) and finally chicken meat(56%; 2.7 x 106 cfu/g).